A transitive perspective on the relief of psychosomatic symptoms - Tschugguel, Walter (Frontiers in Psychology, 2022)
A key element of successful psychotherapy for psychosomatic disorders is that patients change the meaning of their experiences. These changes are brought about by appropriate verbal referencing of the currently experienced symptoms. This theoretical paper argues that these changes are not based on better, more adaptive narratives per se, but on the transition (or linkage) process itself that is experienced between different narratives (or aspects). This view is theoretically justified in various ways. Firstly, through contemporary spatiotemporal neuroscience, which aims to connect mental and structural aspects via a common dynamic property or, according to Georg Northoff, the "common currency" of a brain’s orientation along its embeddedness in its contextual world, i.e., body and environment. Secondly, through the concept from physics of "spontaneous symmetry breaking," this is used analogously to „suffering from symptoms”. If the sufferer is willing to experience a process of "going back," i.e., moving away from the previous narrative (or aspect) by verbally relating to the felt aspects of the symptom in question, i.e., approaching its meaning, the sufferer is moving toward symmetry or an underlying dynamic alignment with his or her world context. Clinical predictions are derived from the theoretical arguments.